AUGMENTED REALITY VIRTUAL DRESSING ROOM BERBASIS ANDROID - Fazlia, Ririn; Anwar, Anwar; Hidayat, Hari Toha (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
Augmented Reality Virtual Dressing Room is a solution for the high percentage of product mismatch issues ordered through online-shop with the actual size of the order. This application will not only be able to satisfy the suitability of goods purchased by consumers but also can be a special attraction for online stores that use it. This study aims to determine the effective distance to perfect output in VDR applications, capacity and device resolution required for the application can run well and to find out the output of virtual clothes if the detection is different. Augmented Reality Application Virtual Dressing Room is an application that runs on the Android mobile platform. This application requires a good device capacity and camera resolution so that the camera on the device can be open, can track, and detect markers by using a marker based tracking system. After the marker is detected, a 3D shirt model will appear above the marker. Based on the results of the test, the effective distance is obtained for a camera that can detect markers perfectly, which is 30cm to 50cm. The distance needed by the user with the camera to be able to adjust the size of the shirt is 1 meter. The device capacity needed to run the application is 2GB up to 4GB with a camera resolution starting from 13MP. For discrepancies in the size of the clothes recommended by the application system can be overcome by rearranging the distance of the device with the marker, the marker distance with the user and the pose of the user. Keywords: Augmented Reality, Virtual Dressing Room, Marker Based Tracking